Quantitative proteomics reveal antidepressant potential protein targets of xiaochaihutang in corticosterone induced model of depression. (1st March 2019) - Zhang, Kuo; He, Meiyao; Su, Dongmei; Pan, Xing; Li, Yuting; Zhang, Haotian; Yang, Jingyu; Wu, Chunfu
Abstract: Ethnopharmacological relevance: Xiaochaihutang (XCHT), one of famous Chinese herbal prescription for treating Shaoyang symptom, has been used successfully in depressive disorders for many years. Our laboratory has demonstrated that XCHT remarkably alleviated various depressive behaviors induced by several depressive animal models, but previous studies only focused on one or several protein targets, lacked dynamic change and interrelation of proteins. Therefore, potential protein targets and mechanisms are required further systematic investigation. Aim of the study: To discover and assess the differentially expressed proteins (DEPs) of hippocampus after oral administration of XCHT in corticosterone (CORT) induced model of depression by using isobaric tags for relative and absolute quantification (iTRAQ) analysis. Materials and methods: The antidepressant effects of XCHT were assessed by two behavioral despair models (forced swimming test and tail suspension test) in CORT induced model of depression. The DEPs of hippocampus after XCHT treatment were investigated by iTRAQ analysis. Potential protein targets and mechanisms were assessed by gene ontology (GO), Kyoto encyclopedia of gene and genomes (KEGG) and protein-protein interaction (PPI) network. Results: Our data demonstrated XCHT could significantly improve depressive behaviors. A total of 241 DEPs were identified after XCHT treatment, including 68 up regulation and 173 down regulation proteins. GO enrichment results indicated that XCHT mainly regulated intracellular structural proteins involved in cellular response to stress, transferase activity and steroid hormone. KEGG enrichment analysis showed that endocytosis might be the principal pathway of XCHT on depression. PPI analysis predicted cell division cycle and apoptosis regulator protein 1 (Ccar1) and Calretinin (Calb2) might play the central roles in XCHT's antidepressant network. Conclusion: Our results indicate that XCHT plays the important roles in antidepressant action by restoring DEPs, which results in the dysregulation of hippocampal neurogenesis, neurotransmitter and steroid hormone. The current results wish to provide novel perspectives for revealing the potential protein targets of XCHT on depression. Graphical abstract: